4D printing 1 : between disruptive research and industrial applications - Demoly, Frédéric; André, Jean-Claude (Systems and industrial engineering series., 2022)
Any time objects and their (self-)organization are to be put into use, their models and methods of thinking as well as their designing and manufacturing need to be reinvented. 4D printing is a future technology that is capable of bringing 3D objects to life. This ability, which gives objects the power to change shape or properties over time through energy stimulation from active materials and additive manufacturing, makes it possible to envisage technological breakthroughs while challenging the relationship between people and objects. 4D Printing 1 presents the different facets of this technology, providing an objective, critical and even disruptive viewpoint to enable its existence and development, and to stimulate the creative drive that industry, society and humanity need in the perpetual quest for evolution and transformation.